What factors facilitate partnerships between higher education and local mental health services for students? A case study collective - Michael Barkham; Gillian Hardy; Kirsty Nisbet; Emma Broglia; Claire Bone; Melanie Simmonds-Buckley; Louise Knowles; Laura Gibbon (BMJ Open)
Background Higher education institutions face challenges in providing effective mental health services for diverse student needs. In the UK, discrepancies between healthcare and education service provision create barriers for students and require stronger alignment through partnerships.Objectives This study aimed to identify risks, barriers and enablers to developing service partnerships between universities and the National Health Service (NHS) in England. It investigated existing partnerships and strategies that facilitate effective collaborative working.Design and setting A case study approach was employed, including coproduction and stakeholder involvement with staff and service users, to gather information from eight English universities developing regional student mental health hubs. This research received appropriate ethical approval.Participants In total, 27 professional staff from counselling, mental health, disability and well-being services participated and represented their respective services.Outcome measures Descriptive information was collected from service websites, handbooks, reports and 11 focus groups using a standardised data collection template. Inter-rater reliability was used to determine the agreement between coders and finalise focus group themes. EQUATOR (Enhancing the QUAlity and Transparency Of health Research) Standards for Reporting Qualitative Research were adopted.Results Using inductive thematic analysis, five themes were identified for developing partnerships: building blocks, facing barriers, achieving positive outcomes, shaping student services and developing coordinated care. Fleiss’ kappa showed strong agreement between raters regarding the partnership factors (k=0.84 (95% CI 0.81 to 0.87), p<0.0005). Effective communication, shared understanding and trust were essential. Barriers included restrictions to information sharing and incompatible data infrastructures between services.Conclusions Stronger partnerships between universities and NHS are needed to meet increasing student mental health demands. Addressing barriers and implementing strategies to develop partnerships can enhance student services.Preregistration https://osf.io/u54qk/